Gochnatia glutinosa (D.Don) D.Don ex Hook. & Arn.: A plant with medicinal value against inflammatory disorders and infections - Mariana Leal; María Inés Mercado; María Alejandra Moreno; José Javier Martínez Chamas; Iris Catiana Zampini; Graciela Inés Ponessa; Mario J. Simirgiotis; María Inés Isla (Heliyon, 2023)
Gochnatia glutinosa is a shrub that grown in the Argentinean semiarid region (Monte region) used in the ancestral medicine as an antiseptic and anti-inflammatory agent.This study was aimed to examine the morpho-anatomical characteristics of G. glutinosa aerial parts, identify the chemical composition of traditionally used preparations to assess its pharmacobotanical characterization and evaluate its activity as antiseptic and anti-inflammatory to give scientific support to its traditional uses. G. glutinosa morpho-anatomical description was performed following standard histological techniques. Tincture and infusion of its aerial parts were prepared and were subjected to phytochemical analysis. Xanthine oxidase (XOD) and lipoxygenase (LOX) inhibition experiments, as well as ABTS•+, superoxide radical, and hydrogen peroxide scavenging activity, were carried out. The growth inhibition of methicillin-resistant Staphylococcus aureus (MRSA) strains was also determined.The morpho-anatomical traits of G. glutinosa leaves and stems were reported for the first time. The medicinal preparations exhibited a large amount of phenolic chemicals mainly flavonoids such as rhamnetin, arcapillin, rhamnacin, hesperetin, isorhamnetin, centaureidin, europetin 7-O-mehylmyricetin, cirsiliol, sakuranetin, genkwanin and eupatorine and also phenolic acids and diterpenoid derivatives. Both preparations had free radical scavenging activity and were able to reduce both XOD and LOX activity, indicating their anti-inflammatory properties. Besides, tincture was effective against all MRSA strains (MIC values ranging from 60 to 240 g DW/mL).The results obtained in this work scientifically support the medicinal popular use of G. glutinosa as an antiseptic and anti-inflammatory. The identification of bioactive compounds and their morpho-anatomical description contribute to the quality control of this medicinal plant from Argentine Calchaquí Valley.